8 'palliative critical care': evolution of a hospital palliative care service in the intensive care unit setting. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Crispin, HK; Haynes, K; Cran, A; Murphy, E; Chambers, R; Davis, CL
Abstract : Introduction: A collaborative approach between the General Intensive Care Unit (GICU) and the Hospital Specialist Palliative Care Team (HSPCT) can promote optimisation of patient physiology and symptom burden, aid clinical decision making, expedite transfer or discharge plans and provide additional support to patients, families and staff. In 2014 we created 4 hours of intensivist time for palliative care and developed joint working, named 'Palliative Critical Care'. In 2016 a weekly combined Palliative Medicine and GICU ward round was established. Here, we detail the impact of this intervention on the activity of the HSPCT and associated patient outcomes. Methods: A retrospective review of HSPCT records of GICU referrals between March 2013 and March 2017. Results: There has been a sustained increase in referrals from GICU to the HSPCT since 2013; 6 in 2013/2014, 57 in 2014/2015, 99 in 2015/16, 89 in 2016/17. Timeliness of referrals has improved. The proportion of patients who died before HSPCT review has reduced, 15.8% in 2014/2015, 7.6% in 2015/16, 10.1% in 2016/2017. Collaborative working has supported patient preferences, enabling direct discharge from GICU to home or hospice in a number of cases (0% prior to intervention, 13.3% in 2014/2015, 2% in 2015/2016, 6.4% in 2016/2017). Over the years, of those transferred to wards 12.5%–22% are discharged home and 13.6%–20.8% to a hospice. The majority of patients seen by the HSPCT are kept under review whilst in hospital, even if discharged from GICU (66.0%–89.7%). Patient and family feedback has been 'excellent'. Conclusion: This intervention has resulted in sustained improvements in collaborative working between the GICU and the HSPCT as indicated by the number and timeliness of referrals. It has supported patient preferences, enabling a significant proportion to be discharged either to home or hospice, including some directly from GICU.